Hepatomegaly and splenomegaly in Oreochromisniloticus cultivated in cages system - Raghiante, Fernanda [UNESP]; Ferrasso, Marina de Mattos [UNESP]; Rodrigues, Marianna Vaz [UNESP]; Biondi, Germano Francisco [UNESP]; Martins, Otavio Augusto [UNESP] (Univ Federal Ceara, Centro Ciencias Agrarias, 2016)
The hepatomegaly and splenomegaly are changes in mass and/or size of the liver and spleen, respectively. This study aims to assess the presence of hepatomegaly and splenomegaly in Oreochromis niloticus cultivated in cages system. Were collected 150 animals of three different refrigerators (A, B and C) who received the fish of cages system. After necropsy, the quantities of hepatomegaly and splenomegaly were measured. The main results show that 24.66% of the fish showed morphological changes in the liver and spleen. We conclude that hepatomegaly and splenomegaly can cause metabolic disorders and therefore, losses in the production of Oreochromisniloticus.
Keywords: Hepatomegaly; Splenomegaly; Oreochromis niloticus